Anomalous right coronary artery from distal left circumflex coronary artery: a rare case report - Bagga, Ashima; Kaul, Diptiman; ., Shubham (International Journal of Advances in Medicine, 2022)
Coronary artery anomalies (CAAs) being a group of congenital disorders, present with highly variable manifestations and have diverse pathophysiological manifestations. In middle aged to elderly patients, a coronary anomaly is often an incidental finding. We presented a case of 65-year-old female with history of diabetes for past 9 years who presented to our emergency department with history of exertional chest pain for past 4 weeks. Anomalous origin of right coronary artery (RCA) from distal left circumflex artery (LCX) was observed on coronary angiography. Patient was managed with optimised medical therapy (OMT).